Effects of temperature at constant air dew point on leaf carboxylation efficiency and CO 2 compensation point of different leaf types - Weber, J. A.; Tenhunen, J. D.; Lange, O. L. (Planta, 1985)
The effect of temperature on photosyn- thesis at constant water-vapor pressure in the air was investigated using two sclerophyll species, Ar- butus unedo and Quercus suber, and one meso- phytic species, Spinacia oleracea. Photosynthesis and transpiration were measured over a range of temperatures, 20-39 ~ C. The external concentra- tion of CO 2 was varied from 340 ~tbar to near CO 2 compensation. The initial slope (carboxylation effi- ciency, CE) of the photosynthetic response to inter- cellular CO 2 concentration, the CO 2 compensation point (/-), and the extrapolated rate of CO 2 re- leased into COa-free air (Ri) were calculated. At an external CO 2 concentration of 320-340 labar CO2, photosynthesis decreased with temperature in all species. The effect of temperature on F was similar in all species. While CE in S. oleracea changed little with temperature, CE decreased by 50% in Q. suber as temperature increased from 25 to 34 ~ C. Arbutus unedo also exhibited a de- crease in CE at higher temperatures but not as marked as Q. suber. The absolute value of Ri in- creased with temperature in S. oleracea, while changing little or decreasing in the sclerophylls. Variations in F and Ri of the sclerophyll species are not consistent with greater increase of respira- tion with temperature in the light in these species compared with S. oleracea.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature-humidity); Sclerophyll; Transpiration

Changes in photosynthetic capacity, carboxylation efficiency, and CO 2 compensation point associated with midday stomatal closure and midday depression of net - Tenhunen, J D; Lange, O L; Gebel, J (Planta, 1984)
The carbon-dioxide response of photo- synthesis of leaves of Quercus suber, a sclerophyl- lous species of the European Mediterranean re- gion, was studied as a function of time of day at the end of the summer dry season in the natural habitat. To examine the response experimentally, a "standard" time course for temperature and hu- midity, which resembled natural conditions, was imposed on the leaves, and the CO 2 pressure exter- nal to the leaves on subsequent days was varied. The particular temperature and humidity condi- tions chosen were those which elicited a strong sto- matal closure at midday and the simultaneous de- pression of net CO 2 uptake. Midday depression of CO 2 uptake is the result of i) a decrease in CO2- saturated photosynthetic capacity after light satu- ration is reached in the early morning, ii) a de- crease in the initial slope of the CO 2 response curve (carboxylation efficiency), and iii) a substantial in- crease in the CO 2 compensation point caused by an increase in leaf temperature and a decrease in humidity. As a consequence of the changes in pho- tosynthesis, the internal leaf CO 2 pressure re- mained essentially constant despite stomatal clo- sure. The effects on capacity, slope, and compensa- tion point were reversed by lowering the tempera- ture and increasing the humidity in the afternoon. Constant internal CO 2 may aid in minimizing photoinhibition during stomatal closure at midday. The results are discussed in terms of possible tem- perature, humidity, and hormonal effects on pho- tosynthesis.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature- humidity); Quercus; Sclerophyll